I vilken utsträckning kan hästar enbart utfodras med grovfoder? - Ferm, Emelie (SLU/Dept. of Animal Nutrition and Management (until 231231), 2011)
Horses are grazers with a digestive system that is adapted for a high fiber diet. Forage is a fiber rich feed that includes grass and legumes. A deficiency of forage and an excess of grains may cause gut disturbances and stereotypic behavior. The aim of this literature study was to summarize information on the horse’s capacity to consume forage-only diets with focus on the horse’s need of energy and protein. The results suggest that all horses are able to consume forage-only diets, which is also shown in previous studies. The forage needs to be equivalent to the horse’s nutrient requirement and consumption capacity. The energy content or the protein content of the forage can be a limiting factor. The nutritive value depends on different pre- and postharvest factors, especially the plant maturity. There are also other aspects that affect if horses will be able to satisfy their nutrient requirement by forage-only diets.